1975
DOI: 10.1136/ard.34.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of proteoglycan and collagen induced in pig articular cartilage in organ culture.

Abstract: . (1975). Annals of the Rheumatic Diseases, 34, 303-311. Breakdown of proteoglycan and collagen induced in pig articular cartilage in organ culture. Explants of articular cartilage from young pigs were maintained in organ culture for 10-16 days, and degradation of matrix was induced by retinol or complement-sufficient antiserum. The percentage breakdown of proteoglycan and collagen (as hydroxyproline release) was measured. The response of the cartilage depended on whether or not the explants were cut so as to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 8 publications
2
42
1
Order By: Relevance
“…Degradation of PGs occurs early in joint damage. The fragments of PGs are released into the synovial fluid and subsequently the blood [72,73]. This hypothesis is supported by the fact that KS levels in patients with MPS I, II, and VI are more elevated, compared with that in MPS III that results in less marked skeletal dysplasia.…”
Section: Secondary Elevation Of Kssupporting
confidence: 62%
“…Degradation of PGs occurs early in joint damage. The fragments of PGs are released into the synovial fluid and subsequently the blood [72,73]. This hypothesis is supported by the fact that KS levels in patients with MPS I, II, and VI are more elevated, compared with that in MPS III that results in less marked skeletal dysplasia.…”
Section: Secondary Elevation Of Kssupporting
confidence: 62%
“…That the chondrocytes of isolated cartilage in culture, when stimulated by retinol in a concentration of 10 iu/ml medium, can digest the proteoglycan and to a lesser extent the collagen of the matrix has been demonstrated in previous work (9).…”
Section: Discussionmentioning
confidence: 97%
“…Van Gieson's stain colors the collagen of normal cartilage matrix a bright red, but when degradation of the collagen is in progress this coloration becomes increasingly faint and eventually is lost. Previous biochemical studies (9) have demonstrated a close qualitative correspondence between these staining reactions and the proteoglycan and collagen content of the cartilage.…”
Section: His T Ol O G Y Fixationmentioning
confidence: 99%
“…It is known that the degradation of proteoglycans occurs early in joint damage (43) and that fragments are released into the synovial fluid and subsequently the serum (44,45). The quantitation of keratan sulfates in both serum and synovial fluid has therefore been proposed as a measure of cartilage breakdown.…”
Section: Discussionmentioning
confidence: 99%